Currency Wars and Trade - Kris James Mitchener; Kirsten Wandschneider (CESifo GmbH, 2024)
The Great Depression is the canonical case of a widespread currency war, with more than 70 countries devaluing their currencies relative to gold between 1929 and 1936. What were the currency war's effects on trade flows? We use newly-compiled, highfrequency bilateral trade data and gravity models that account for when and whether trade partners had devalued to identify the effects of the currency war on global trade. Our empirical estimates show that a country's trade was reduced by more than 21% following devaluation. This negative and statistically significant decline in trade suggests that the currency war destroyed the trade-enhancing benefits of the global monetary standard, ending regime coordination and increasing trade costs.
Keywords: F14; F33; F42; N10; N70; 330; currency war; monetary regimes; gold standard; competitive devaluations; "beggar thy neighbour"; gravity model